2020
DOI: 10.1016/j.dsx.2020.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Teledentistry during COVID-19 pandemic

Abstract: Background and aims: Dentistry involves close face-to-face interaction with patients, hence during the COVID-19 pandemic, it has mostly been suspended. Teledentistry can offer an innovative solution to resume dental practice during this pandemic. In this review, we provide a brief overview of applications of teledentistry. Methods: Articles on teledentistry, relevant to this review, were searched and consulted from PubMed, Google Scholar, and Cochrane database. Results: Teledentistry is the remote facilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
211
0
30

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(280 citation statements)
references
References 26 publications
2
211
0
30
Order By: Relevance
“…Almost all of the respondents in the current study stated that they had altered their appointment schedules to control the spread of the virus. This process could be started by initially calling patients or having video conferences to identify their need and decide if their condition requires clinical intervention (34). This could help in limiting face-to-face contact, making diagnoses through remote dental screening, deterring any COVID-19 susceptible patients, delaying nonemergency work, and planning effectively for the emergency cases (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the respondents in the current study stated that they had altered their appointment schedules to control the spread of the virus. This process could be started by initially calling patients or having video conferences to identify their need and decide if their condition requires clinical intervention (34). This could help in limiting face-to-face contact, making diagnoses through remote dental screening, deterring any COVID-19 susceptible patients, delaying nonemergency work, and planning effectively for the emergency cases (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…Information about them was displayed over the website of the health care centre as well signboards were placed on the walls of physical units of the centre. This facility provided necessary education, guidance, consultation, appointment and referral for the dental care or treatment, hence unnecessary contact was minimised [ 34 ]. The second concept in the wake of minimisminimising human contact which gained wide success was Telephone triaging/teletriaging.…”
Section: Dental Radiology and Covid-19mentioning
confidence: 99%
“…It has been shown that some dentists are affected by COVID in Indonesia and Thailand. In Indonesia, 24 medical professionals, including six dentists, have died in the country from COVID-19 [20]. The reason for high COVID cases in medical and dental practitioners may be due to The Indonesian dental association had not advised dentists to close their practices or to postpone nonemergency treatment.…”
Section: Impact Of Covid-19 Virus In Dentistrymentioning
confidence: 99%